Developmental defects in planarian hatchlings (Platyhelminthes: Rhabditophora) - Xiaoting Dai; Jacob Sobota; Xinghua Li; Longhua Guo (Zoologia (Curitiba))
ABSTRACT Developmental plasticity of the planarians is well-illustrated by whole-body regeneration from any tissue fragments and body size scaling regulated by food intake. Here we report another form of developmental plasticity that appears to be shared by multiple planarian species. We have observed developmental defects at rates up to ~10% in batches of Schmidtea mediterranea (Benazzi, 1975) and Schmidtea polychroa (Schmidt, 1862) hatchlings. The most frequent defect is duplicated body parts which occurs in both two species, which can be corrected after amputation and regeneration, supporting that these developmental defects were not caused by genetic mutations. Taken together, our data described a new form of developmental plasticity and an interesting comparison between development and regeneration in the hatchlings of freshwater planarians, that the two processes can have different outcomes.